2019
DOI: 10.1007/jhep03(2019)106
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the three-particle quantization condition including higher partial waves

Abstract: We present an implementation of the relativistic three-particle quantization condition including both sand d-wave two-particle channels. For this, we develop a systematic expansion of the three-particle K matrix, K df,3 , about threshold, which is the generalization of the effective range expansion of the two-particle K matrix, K 2 . Relativistic invariance plays an important role in this expansion. We find that d-wave two-particle channels enter first at quadratic order. We explain how to implement the result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
195
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(198 citation statements)
references
References 102 publications
(338 reference statements)
2
195
0
1
Order By: Relevance
“…One way to see that this is indeed the case is to use the threshold expansion developed in Ref. [38]. At any order in the expansion parameter ∆, one can show that the only terms that are purely s-wave are those that are isotropic.…”
Section: S-wave Approximationmentioning
confidence: 98%
See 3 more Smart Citations
“…One way to see that this is indeed the case is to use the threshold expansion developed in Ref. [38]. At any order in the expansion parameter ∆, one can show that the only terms that are purely s-wave are those that are isotropic.…”
Section: S-wave Approximationmentioning
confidence: 98%
“…The procedure for decomposing the QC in this case was first presented in Ref. [38], but the generalization to arbitrary P is new to this work and deserves explanation. Unlike in Ref.…”
Section: Block-diagonalization Of the Quantization Conditionmentioning
confidence: 98%
See 2 more Smart Citations
“…[38]; higher-spin twoparticle sub-systems were considered in Ref. [57]. First numerical studies [4,35,37] demonstrated the feasibility of different formalisms.…”
Section: Introductionmentioning
confidence: 99%